Digital forensics tools improvement based on artificial intelligence - Floderus, S.; Rosenholm, L. (ХНУРЕ, 2020)
The digital world is rapidly growing with new devices, smartphones and internet users. In addition, the Internet of Things is contributing to many more devices in circulation. This heavy number of devices also correlates with an increase in cybercrime. Current resources regarding law enforcement are very limited, while tools and techniques within digital forensic require human interaction and a great amount of time. With the use of artificial intelligence and machine learning, there are possibilities to improve current techniques and automate some parts of the process.